Applied Aerodynamics: A Digital Textbook - Kroo, I.
This text was developed for a course in applied aerodynamics at Stanford University. The first year graduate course includes topics ranging from a review of the basic, governing equations of fluid flow to practical issues related to airfoil and wing design. The course included approximately 26 lectures dealing with the basic topics, with weekly problem sets to encourage students to explore topics more fully. These notes were used as part of the course reading materials. It is impossible to discuss applied aerodynamics without reference to computational methods, and the course makes use of several programs for aerodynamic analysis of airfoils and wings, limited versions of which are included here. The material presented here complements a separate course in compressible flow theory, and many important issues are left to that course, while a continuation of this material is given in courses on advanced aerodynamic topics and aircraft design. This digital text is intended to supplement a more conventional textbook in applied aerodynamics. The material has been composed based on lecture notes over the last few years and is continually under development, so your comments and suggestions are helpful.